2018
DOI: 10.1093/geront/gny036
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal Analysis of the Relationship Between Purposes of Internet Use and Well-being Among Older Adults

Abstract: Findings highlight that Internet use can support older adults' well-being; however, not every form of engagement impacts well-being the same way. These findings will inform the focus of interventions which aim to promote well-being.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
159
0
5

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 185 publications
(180 citation statements)
references
References 33 publications
16
159
0
5
Order By: Relevance
“…In conclusion, we found that older adults' perceptions of emotional support are enhanced by participation in social activities and associated group identification, and those perceptions, in turn, affect their sense of belonging and SWB. Our findings offer insights into the mixed evidence about the effect of activity participation on sense of belonging for older adults (Bailey & McLaren, 2005;Laukka, 2007;Szabo et al, 2019). These findings also contribute to the SIA (Cruwys et al, 2014;S.…”
Section: Resultssupporting
confidence: 55%
“…In conclusion, we found that older adults' perceptions of emotional support are enhanced by participation in social activities and associated group identification, and those perceptions, in turn, affect their sense of belonging and SWB. Our findings offer insights into the mixed evidence about the effect of activity participation on sense of belonging for older adults (Bailey & McLaren, 2005;Laukka, 2007;Szabo et al, 2019). These findings also contribute to the SIA (Cruwys et al, 2014;S.…”
Section: Resultssupporting
confidence: 55%
“…First, because participants were non-randomly sampled internet users, it is possible that their levels of loneliness systematically differ from the rest of the population. In fact, research suggests that internet use significantly decreases loneliness [98][99][100][101][102], contributes to well-being and sense of empowerment by affecting interpersonal interactions [103], and reduces the probability of depression by one third in older adults [104]. That said, internet use among older adults has increased significantly over time [105], with 67% of adults ages 65 and above using the internet in 2016 [106].…”
Section: Discussionmentioning
confidence: 99%
“… 4 , 5 Recent studies argued that the contribution to SWB depends on the type and purpose of use. Delineating three distinct purposes common among older users ( communication, information, and task performance ), one study 6 found that all three indirectly impacted SWB via increased social engagement. Another study, 7 however, examined leisure in addition to the above three purposes and showed that after controlling for sociodemographic variables, only leisure uses (enjoyable online activities such as games, music, films, hobbies, blog writing, and many more) associated significantly with SWB.…”
Section: Introductionmentioning
confidence: 99%